CTF143 : Idea and storytelling / College of Creative Arts - UiTM, College of Creative Arts (Universiti Teknologi MARA (UiTM), 2023)
Students are trained to observe, to imagine and to employ their power of visualization to enhance their process of creative and critical thinking. The degree of imagination that they have will help them to formulate ideas and enable them to develop the narrative techniques of storytelling. The concept of storytelling and its style will be translated into writing. The idea that is written will be used as a blueprint for film making, stage presentations or TV programs.